2020
DOI: 10.1111/dom.13980
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased hepatic insulin clearance and change in serum triglycerides or β‐hydroxybutyrate concentration via the sodium/glucose‐cotransporter 2 inhibitor tofogliflozin

Abstract: Aims: Obesity and hepatic fat accumulation diminish hepatic insulin clearance, which can cause hyperinsulinaemia. Sodium/glucose-cotransporter 2 inhibitors (SGLTis) improve insulin resistance and hyperinsulinaemia by weight loss via increased urinary glucose excretion in type 2 diabetes. However, there are few reports of the influence of SGLT2is on hepatic insulin clearance. We examined the impact of an SGLT2i on hepatic insulin clearance and explored the clinical influence associated with changes in hepatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Previous reports have demonstrated that a surrogate marker of insulin clearance during a meal load test is higher after a single dose of an SGLT2i or chronic treatment [ 34 , 35 ]. However, it remains unclear whether SGLT2i treatment alters systemic insulin clearance as measured by a hyperinsulinemic euglycemic clamp study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have demonstrated that a surrogate marker of insulin clearance during a meal load test is higher after a single dose of an SGLT2i or chronic treatment [ 34 , 35 ]. However, it remains unclear whether SGLT2i treatment alters systemic insulin clearance as measured by a hyperinsulinemic euglycemic clamp study.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrannini et al reported that single-dose or 4-week administration of empagliflozin increased insulin clearance [34]. Very recently, similar results were obtained after 24 weeks of tofogliflozin treatment [35]. The mechanisms by which insulin clearance increases after SGLT2i treatment are currently unknown.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, SGLT2i can improve glycemic regulation via an insulin-independent mechanism (Ferrannini and Solini, 2012). The therapeutic application of SGLT2i could lead to weight loss (Merovci et al, 2014), correction of hyperinsulinemia (Matsubayashi et al, 2020), and reduced hyperleptinemia (Vickers et al, 2014). SGLT2i could also modulate inflammation via IL-1β (Nakatsu et al, 2017) and Nlrp3 inflammasome (Sukhanov et al, 2021).…”
Section: Sglt2 Inhibitors Can Increase the Production Of β-Ohbmentioning
confidence: 99%
“…Dapagliflozin reduces liver fat but did not affect tissue insulin sensitivity of the liver, muscle, and adipocyte (23). Recent another study also reported that SGLT2i increased hepatic insulin clearance (24). SGLT2i increases glucagon section from alpha cells (25).…”
Section: Discussionmentioning
confidence: 93%